ISSUES AND PROBLEMS IN BRAIN MAGNETIC RESONANCE IMAGING: AN OVERVIEW - Novanto Yudistira; Daut Daman (Universitas Ahmad Dahlan, 2008)
There are many issues and problems in the brain magnetic resonance imaging (MRI) area that haven’t solved or reached satisfying result yet. This paper presents an overview of the various issues and problems of the segmentation, correction, optimization, description and their application in MRI. The overview is started by describing the segmentation properties that are the most important and challenging in MRI brain manipulation. Then correction for reconstructing the brain MRI cortex, classification is utilized to classify the segmented brain image, and also review the uses of description is the great prospecting issue while some neurologist need the information resulted from brain imaging process including their potential problems from application applied by each technique. In each case, it is provided some general background information.